2009
DOI: 10.1177/0091270009334376
|View full text |Cite
|
Sign up to set email alerts
|

Statin Effects on LDL and HDL Cholesterol in South Asian and White Populations

Abstract: Inasmuch as statins appear to exhibit altered efficacy in some Asian populations (predominantly East Asian), current lipid guidelines recommend the use of lower statin doses in all Asians. Whether this should also apply to South Asians, a population at high risk for coronary heart disease, remains unclear. The authors evaluated the lipid-modifying effects of statins in South Asian and white patients with established coronary heart disease. Atorvastatin (median dose=20 mg/d in both groups) produced similar decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Furthermore, we cannot exclude that lipid levels among GLMs users from African origin are lower, but in the atherosclerosis risk in communities study (ARIC) population study of cardiovascular risk factors among African-American compared to White subjects, no differences were found in lipid levels (Hozawa et al, 2007), which is also consistent with the review by Kurian et al of studies focusing on the African population (Kurian and Cardarelli, 2007). Even though metabolic parameters seem to differ between Eastern and Western populations (De Silva et al, 2007; Christensen et al, 2009; Likhari and Gama, 2009), it is unlikely that the subjects from Eastern countries in Denmark have less need of statins as persons from certain Eastern countries around the world have been identified as being at particularly high risk of coronary heart disease and of diabetes (McKeigue, 1989; Fischbacher et al, 2009; Gupta et al, 2009) Hence, subjects from Eastern countries with diabetes living in Denmark receive which probably inadequate statin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we cannot exclude that lipid levels among GLMs users from African origin are lower, but in the atherosclerosis risk in communities study (ARIC) population study of cardiovascular risk factors among African-American compared to White subjects, no differences were found in lipid levels (Hozawa et al, 2007), which is also consistent with the review by Kurian et al of studies focusing on the African population (Kurian and Cardarelli, 2007). Even though metabolic parameters seem to differ between Eastern and Western populations (De Silva et al, 2007; Christensen et al, 2009; Likhari and Gama, 2009), it is unlikely that the subjects from Eastern countries in Denmark have less need of statins as persons from certain Eastern countries around the world have been identified as being at particularly high risk of coronary heart disease and of diabetes (McKeigue, 1989; Fischbacher et al, 2009; Gupta et al, 2009) Hence, subjects from Eastern countries with diabetes living in Denmark receive which probably inadequate statin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In an observational, prospective study in Canada, no difference in the magnitude of LDL-C lowering was observed among non-Hispanic whites and South Asians (−41% vs. −43%, respectively; P=0.40), taking atorvastatin or simvastatin (20 mg median dose for each) for more than three years in the secondary prevention of CVD 62 …”
Section: Treatment Of Dyslipidemiamentioning
confidence: 94%
“…

In combined analysis of two small multicenter open-label studies, GOALLS (included non-Asian and Asian participants) and STATT (included Asians only), the authors compared cholesterol outcomes among patients with coronary heart disease treated with simvastatin for 14 weeks. 61 There were no differences in changes in LDL-C among Asians in the STATT study (N=133; −45.4 mg/dL) relative to Asians (N=15) or non-Asians (N=183) in the GOALLS study (−41.1 mg/dL and −41.2 mg/dL, respectively) 61

In an observational, prospective study in Canada, no difference in the magnitude of LDL-C lowering was observed among non-Hispanic whites and South Asians (−41% vs. −43%, respectively; P=0.40), taking atorvastatin or simvastatin (20 mg median dose for each) for more than three years in the secondary prevention of CVD 62 Using data from an RCT evaluating atorvastatin versus placebo in a multi-ethnic population in the U.K., Chapman and colleagues matched White (N=198) and South Asian (N =76) cohorts receiving atorvastatin to evaluate the effects of statins across race/ethnic groups. 63 The authors again found no difference in the percent reduction in LDL-C among whites and South Asians (−40% vs. −39%; P=0.92) 63
…”
Section: Treatment Of Dyslipidemiamentioning
confidence: 99%
“…The 2006 Canadian dyslipidemia guidelines suggested using lower statin doses in all Asians [22]. The Prospective Assessment of Cardiovascular Risk and Treatment of Canadians of Varying Ethnicity (PRACTICE) registry evaluated effects of statins in South Asian and Caucasian patients with established CAD [23]. After 6 weeks of treatment, atorvastatin 20 mg/d produced similar decreases in LDL-C in South Asian (43%) and Caucasian (41%) patients and raised HDL-C by 19% in South Asians and by 12% in Caucasians.…”
Section: Discussionmentioning
confidence: 99%